Heat-solubilized curry spice curcumin inhibits antibody-antigen interaction in in vitro studies: A possible therapy to alleviate autoimmune disorders - Kurien, Biji T. (2010)
Chronic and complex autoimmune diseases, currently treated palliatively with immunosuppressives, require multi-targeted therapy for greater effectiveness. The naturally occurring polyphenol curcumin has emerged as a powerful “nutraceutical” that interacts with multiple targets to regress diseases safely and inexpensively. Upto 8 g/day of curcumin for 18 months was non-toxic to humans. However, curcumin's utility is limited by its aqueous insolubility. We have demonstrated a heat-mediated 12-fold increase in curcumin's aqueous solubility. Here we show by, SDS-PAGE and SPR, that heat-solubilized curcumin binds to proteins. Based on this binding we hypothesized that heat-solubilized curcumin or turmeric would prevent autoantibody targeting of cognate autoantigens. Heat-solubilized curcumin/turmeric significantly decreased binding of autoantibodies from Sjögren's syndrome (SS) (up to 43/70 % respectively) and SLE (up to 52/70 % respectively) patients as well as an animal model of SS (up to 50/60 % respectively) to their cognate antigens. However, inhibition was not specific to autoimmunity. Heat-solubilized curcumin/turmeric also inhibited binding of polyclonal anti-spectrin to spectrin (50/56 % respectively). Thus, we suggest that the multifaceted heat-solubilized curcumin can ameliorate autoimmune disorders. In addition, the non-toxic curcumin could serve as a new protein stain in SDS-PAGE even though it is less sensitive than the Coomassie system which involves toxic chemicals.